2014
DOI: 10.1130/g34900.1
|View full text |Cite
|
Sign up to set email alerts
|

Stylolites in limestones: Barriers to fluid flow?

Abstract: International audienceStylolites--products of intergranular pressure-solution--are laterally extensive, planar features. They are a common strain localization feature in sedimentary rocks. Their potential impact on regional fluid flow has interested geoscientists for almost a century. Prevalent views are that they act as permeability barriers, although laboratory studies are extremely rare. Here we report on a systematic laboratory study of the influence of stylolites on permeability in limestone. Our data dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 21 publications
7
61
1
Order By: Relevance
“…The most important ingredient is the 535 collection of sealing material in the stylolite. If the material is not sealing (as was 536 the case in the study of Heap et al, 2014) the stylolites or part of them cannot be 537 local barriers to fluid flow. In general stylolites can perform three different 538 structural changes to produce barriers: (i) they can collect impermeable material 539 and thus build up a barrier, (ii) they can intensify the existing sealing properties 540 of layers and (iii) they can offset existing barriers ( fig.…”
Section: Barriers and Leaks 532mentioning
confidence: 99%
See 2 more Smart Citations
“…The most important ingredient is the 535 collection of sealing material in the stylolite. If the material is not sealing (as was 536 the case in the study of Heap et al, 2014) the stylolites or part of them cannot be 537 local barriers to fluid flow. In general stylolites can perform three different 538 structural changes to produce barriers: (i) they can collect impermeable material 539 and thus build up a barrier, (ii) they can intensify the existing sealing properties 540 of layers and (iii) they can offset existing barriers ( fig.…”
Section: Barriers and Leaks 532mentioning
confidence: 99%
“…If we perform 564 a two--dimensional analysis of the stylolites shown in figure 1a and b, stylolite 1b 565 has a sealing capability of only 15%, whereas stylolite 1a has a local sealing 566 capability of around 75%. Further research is needed in this direction in order 567 to quantify sealing qualities and local versus larger--scale permeabilities of these 568 complex structures following the work of Heap et al (2014 by the dissolution rate of each particle (1 represents 0 pinning strength). For the 856 matrix 10% of particles dissolve a factor x times the dissolution--rate of the 857 matrix.…”
Section: Barriers and Leaks 532mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many stylolites found within the limestone beds as well, along the planes of which additional points of weakness exist. These lateral stylolitic seams can enhance fluid flow and dissolution along their path, where delamination and cracking can occur (Heap et al 2013), as was observed in the cave. Over time, a breakout dome formed and migrated upward, thinning the bedrock support and creating a situation wherein structural failure and the sinkhole collapse was imminent.…”
Section: Discussionmentioning
confidence: 99%
“…First, it records the intensity of compaction and reflects the expulsion of reservoir fluids during primary migration and, second, it controls the transformation of reservoir from porous to dual, porous-fractured. The systems of tectonic fractures together with the systems of stylolite seams both influnce the migration of reservoir fluids (Stockdale, 1926;Ramsden, 1952;Radlicz, 1966;Dunnington, 1967;Semyrka, 1985;Strzetelski, 1977;Koepnick, 1988;Aydin, 2000;Agosta et al, 2009;Agosta et al, 2010;Heap et al, 2014).…”
mentioning
confidence: 99%